Home-o: Being at Home with Reflections on Hetero-Homosexual Identity. Issue 1 (2nd January 2017) - Nash, Joshua
ABSTRACT: This article presents a creative interpretation of interaction between hetero- and homosexual worlds. The metaphor of home is used to transfer different meanings and experiences of hetero-homosexuality into private and personal takes on bisexuality and being heteroflexible. Self-knowledge is implicitly equated with awareness of one's sexuality.